Kompetensi Pendidik dan Tenaga Kependidikan dalam Meningkatkan Mutu Pendidikan SMP Negeri 3 Kwandang - Dagong, Sukma Windhari; Arsana, I Kadek Satria (Universitas Islam Negeri Raden Intan Lampung, 2019)
AbstracThis study aims to determine the competence of educators and education personnel in improving quality of education. The interview method with the collection of school data and as a resource person is the School Principal as well as the educators and education staff with a long period of research starting from December - January 2018. The results of the study showed: (1) Competence is relatively good, where all teachers are predicated as scholars, have learning tools, apply learning with a cooperative model, already certified, and there are achievers at the national level. Good teacher competency is very influential on the quality of learning and the quality of education. (2) Strategies and methods that are realized by applying Cooperative learning and active, innovative, creative, effective, and fun learning as well as through classroom action research. (3) The values shown by the teacher in the learning process begin with the internalization of values towards the teacher personally in order to become a good personality teacher and at the same time be realized to students through role models in order to realize good personality students. (4) Efforts made by teachers in developing professional competence by attending training, upgrading, workshops, and teacher working groups, as well as making classroom action research. So, improving the quality of education is not immune from the collaboration carried out by educators and education personnel in carrying out their duties and responsibilities so that the quality of education can be achieved.Keywords: Educator Competence, Quality, Principal AbstrakPenelitian ini bertujuan untuk mengetahui kompetensi pendidik dan tenaga kependidikan dalam meningkatkan mutu pendidikan. Metode wawancara dengan pengumpulan data sekolah dan sebagai narasumber adalah Kepala Sekolah serta para pendidik dan tenaga kependidikan dengan lama penelitian mulai Desember - Januari 2018. Hasil penelitian menunjukkan: (1) Kompetensi relatif baik, dimana semua guru berpredikat sarjana, memiliki perangkat pembelajaran, menerapkan pembelajaran dengan model kooperatif, sudah tersertifikasi, dan ada yang berprestasi pada tingkat nasional. Kompetensi guru yang baik sangat berpengaruh kepada kualitas pembelajaran dan mutu pendidikan. (2) Strategi dan Metode yang diwujudkan dengan penerapan pembelajaran Kooperatif dan pembelajaran aktif, inovatif, kreatif, efektif, dan menyenangkan serta melalui penelitian tindakan kelas. (3) Nilai-nilai yang ditunjukkan guru dalam proses pembelajaran diawali dengan internalisasi nilai-nilai terhadap guru secara pribadi agar menjadi guru yang berkepribadian baik sekaligus di realisasikan kepada para siswa melalui keteladanan guna terwujud siswa berkepribadian baik pula. (4) Upaya yang dilakukan guru dalam mengembangkan kompetensi professional dengan mengikuti diklat, penataran, workshop, dan kelompok kerja guru, serta membuat penelitian tindakan kelas. Jadi, peningkatan mutu pendidikan tidak luput dari kerjasama yang dilakukan oleh para pendidik dan tenaga kependidikan dalam melaksanakan tugas dan tanggung jawab sehingga mutu pendidikan dapat dicapai.Kata Kunci : Kompetensi Pendidik, Mutu, Kepala Sekolah